Efektivitas Aplikasi Digital dalam Pelaporan Keuangan di SMPN X - Yuvensius Lana; Siti Nurwanti; Abdul Mutholib; Reo Riki Lazarius; Sisca Septiani; Wiwik Pudjaningsih (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the effectiveness of digital applications in financial reporting at UPTD SMP Negeri X. The focus of the research is to identify the impact of digital technology implementation on the accuracy, transparency, and efficiency of financial reporting in educational institutions. The method used was descriptive qualitative with data collection through semi-structured interviews, participatory observation, and document analysis in the March–May 2024 period. The research respondents consisted of four key personnel: school principals, treasurers, teachers in the field of infrastructure, and teachers in the field of curriculum who have been using the ARKAS application since 2022. The results of the study show that digital applications contribute positively to increasing the effectiveness of financial reporting. This is shown by the average scores on the indicators of accuracy (4.2), transparency (4.1), and timeliness (4.0) on a five-point scale. The implementation of digital systems helps minimize recording errors, speed up the validation process, and increase financial information disclosure. However, the utilization of advanced features such as financial analytics (43.75%), visual reporting (31.25%), and multi-unit integration (25%) is still relatively low. The main challenges found include limited technical training and low digital literacy which is recognized by all respondents (100%). In addition, the lack of supervision from related parties and the limitations of information technology infrastructure are also significant obstacles. Thus, the effectiveness of digital applications is not only determined by the sophistication of the technology used, but also by the readiness of human resources, institutional support, and organizational cultural adaptation. The findings of this study provide important implications for education managers, especially in the formulation of policies to strengthen technology-based governance. Investment in continuous training, infrastructure capacity building, and consistent supervision are key factors to maximize the benefits of digital applications in secondary education financial management.